THE NEED FOR A COMPETENCIES’ ASSESSMENT FRAMEWORK FOR THE MALAYSIAN CONSTRUCTION PROJECT MANAGERS - Chee Moon, Au; Abd-Karim, Saipol Bari; Mohd Danuri, Mohd Suhaimi (Journal of Surveying, Construction and Property, 2018)
For decades, as a developing country, construction industry remains as one of the largest and most important industries in Malaysia especially in terms of job creation. However, project failures in terms of project delay and cost overrun are observed more severe than the global average. While there are many reasons that may contribute to these problems, but recent studies carried out globally by the well-known researchers in project management have found that the competency of project manager, being one of the most important persons from initiating, to closing of the project, is one of the most crucial factor affecting project success. Many developed nations have come out with their project management assessment and certification standards, in order to train, assess, and certify the qualified project managers that are equipped with the necessary and required competencies and skills, but there is an absence of project manager’s competencies assessment and certification standards in Malaysia until to date. This paper presents the literature review that have been carried out on the need for a competencies assessment framework for the Malaysian construction project managers.